Collaborative public administration and administrative procedures - Kovač, Polonca (Teorija in praksa, 2015)
In 2009 an applicative and scientific problem-based research portal of an interdisciplinary character - the Administrative Consultation Wiki (ACW) - was conceived, providing professionally verified and thus reliable information when resolving complex procedural legal dilemmas in administrative matters. The article explores the ACW as a collaborative PA platform inviting different stakeholders to co-participate in the context of identified social, cognitive, and professional boundaries, through boundary spanning. The ACW is evaluated by its holders' goals, a survey of users, and a SWOT analysis, which determined it to be one of the possible ways to systematically enhance the collaboration of PA stakeholders in the form of partnerships and networking in order to strive for good public government and governance.
Keywords: Administrative procedure; Evaluation; Javna uprava; participacija; Public administration; Upravni postopek; Vrednotenje